Pengembangan Karakter Akademik Santri Melalui Musyawarah Keagamaan Di Pondok Pesantren Roudlotut Tholibin - Haikal Abdullah; Ulil Hidayah (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to examine the role of religious deliberation in fostering the academic character of students at Pondok Pesantren Roudlotut Tholibin, particularly in developing critical thinking, scientific communication, and collaborative problem-solving skills related to religious issues. Employing a descriptive qualitative design, data were collected through direct observation and in-depth interviews, and analyzed using a data-display technique to obtain a comprehensive understanding of the implementation of deliberative learning. The findings indicate that structured religious deliberation implemented through general and takhassus curricula, as well as multi-level Bahtsul Masail activities enhances students’ analytical abilities in fiqh, strengthens their argumentative reasoning, and cultivates essential academic values such as intellectual humility, social cohesion, empathy, and public speaking confidence. Participation in inter-pesantren scholarly forums further contributes to students’ intellectual maturity and social competence. The study concludes that Musyawarah Keagamaan serves as an effective pedagogical model for shaping holistic academic character in Islamic boarding school students. Nevertheless, further research with broader institutional coverage is recommended to strengthen the generalizability of these findings.